2020
DOI: 10.1186/s13104-020-05164-5
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphy evaluation of hyperthyroidism and its correlation with clinical and biochemical profiles

Abstract: Objective Hyperthyroidism is the excessive synthesis of thyroid hormones. Thyroid uptake scans and ultrasonography provide an accurate diagnosis of hyperthyroidism, especially when thyroid receptor antibody (TRAb) measurement is not readily available. This study explored the prevalence of various hyperthyroidism causes using retrospective scintigraphy results and evaluated their relationship with clinical, biochemical, and sonographic imaging parameters from patients who underwent 99mTc-pertechnetate thyroid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…Thyrotoxicosis is a frequent reason for referring patients to nuclear medicine centers for radio-iodine therapy, while Grave's disease and toxic nodular goiter are the two most common pathologies causing thyrotoxicosis (1). All of our subjects with a hyperfunctioning thyroid gland had ultrasound findings consistent with either of these two disorders.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Thyrotoxicosis is a frequent reason for referring patients to nuclear medicine centers for radio-iodine therapy, while Grave's disease and toxic nodular goiter are the two most common pathologies causing thyrotoxicosis (1). All of our subjects with a hyperfunctioning thyroid gland had ultrasound findings consistent with either of these two disorders.…”
Section: Discussionmentioning
confidence: 74%
“…Most of the studies observed a correlation between these investigations and the background of diagnosed pathology, e.g., Grave's disease, autoimmune thyroiditis, thyroid malignancy, etc. (1,2). The data we represent is the cross-sectional picture of a tertiary-level institute in southern Dhaka where multitudes of patients are referred in various stages of disease course with a view to not only confirming the diagnosis but also monitoring treatment response and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Using ultrasound diagnostics makes it possible to detect nodular formations in the thyroid gland and suspect these neoplasms' malignant nature. However, for preoperative confirmation of the diagnosis of TNG, patients need a more specific instrumental method of diagnosis -scintigraphy [6].…”
Section: Connection Of the Publication With Planned Research Workmentioning
confidence: 99%
“…Використання ультразвукової діагностики дає змогу виявити вузлові утворення в щитоподібній залозі та запідозрити злоякісний характер даних новоутворень. Однак, для доопераційного підтвердження діагнозу ВТЗ пацієнти потребують більш специфічного інструментального методу діагностикисцинтіграфії [6].…”
Section: вступunclassified
See 1 more Smart Citation